The influence of problem-based learning and discovery learning models on learning outcomes - Ardia Puti Paramitha; Ni'matul Istiqomah; Siti Mastura (Jurnal Penelitian Ilmu Pendidikan, 2023)
Learning outcomes are a way of seeing the ability of students during learning, when they get low learning outcomes, the learning objectives are less channeled. This can be overcome using learning models. The purpose of this study is to determine 1) The influence of the Problem Based Learning model on learning outcomes; 2) The influence of the Discovery learning model on learning outcomes; 3) The influence of differences between the Problem Based Learning and Discovery learning models on learning outcomes in Economics subjects. This study used a quasi-experimental design. The data population in this study is class XI social studies, at one of the high schools in Bojonegoro Regency for the 2021-2022 school year. By taking a sampling technique, namely purposive sampling. This study was conducted in 2022 from April to May. The instrument in this study is a test of learning outcomes in the form of multiple choice. Data analysis using normality test, Wilcoxon signed rank test, and N-Gain test. The results of this study inform that Problem Based Learning and Discovery learning have a positive influence on learning outcomes. Meanwhile, Problem-based learning and discovery learning has a difference, namely in the Problem Based learning group by 71% higher than the discovery learning group by 55%. Based on the results of the study, it can be concluded that the use of problem-based learning and discovery learning can improve student learning outcomes and help students actively participate in learning. The suggestion for further research is to be able to use a variety of learning models.Pengaruh model problem-based learning dan discovery learning terhadap hasil belajarHasil belajar adalah cara melihat kemampuan peserta didik selama menangkap pembelajaran, ketika mendapatkan hasil belajar yang rendah maka tujuan pembelajaran tersebut kurang tersalurkan. Hal tersebut dapat diatasi dengan penggunaan model pembelajaran. Tujuan penelitian ini untuk mengetahui 1)Pengaruh model Problem Based Learning terhadap hasil belajar ; 2) Pengaruh model Discovery learning terhadap hasil belajar; 3) Pengaruh perbedaan antara model Problem Based Learning dan Discovery learning terhadap hasil belajar pada mata pelajaran Ekonomi. Penelitian ini menggunakan desian quasieksperimen. Populasi data dalam penelitian ini ialah kelas XI IPS, di salah satu SMAN di Kabupaten Bojonegoro tahun ajaran 2021-2022. Dengan mengambil sampel teknik yaitu purposive sampling. Penelitian inidilakukantahun 2022 pada bulan april hingga mei. Instrumen didalam penelitian ini ialah test hasil belajar berupa pilihan ganda. Analisis data dengan menggunakan uji normalitas, uji wilcoxon signed rank, dan Uji N-Gain. Hasil dalam penelitian ini menginformasikan bahwa terdapat Model Problem Based Learning dan Discovery learning memiliki pengaruh positif terhadap hasil belajar. Adapun, antara Problem based learning dan discovery learning memiliki perbedaan yaitu pada kelompok Problem Based learning sebesar 71% lebih tinggi dibandingkan dengan kelompok discovery learning sebesar 55%. Berdasarkan hasil penelitian, dapat disimpulkan bahwa penggunaan problem based learning dan discovery learning dapat meningkatkan hasil belajar pserta didik serta membantu peserta didik ikut secara aktif dalam pembelajaran. Saran untuk penelitian selanjutnya yaitu dapat menggunakan model pembelajaran yang bervariasi.